Digital transformation and innovation, dynamic capabilities to strengthen the financial performance of Mexican SMEs: a sustainable approach - Luis Enrique Valdez-Juárez; Elva Alicia Ramos-Escobar; Oscar Ernesto Hernández-Ponce; José Alonso Ruiz-Zamora (Cogent Business & Management, 2024)
The main purpose of the research is to analyze the effect that digital transformation has on technological and non-technological innovation as key factors that increase financial performance in SMEs. The study focuses on a sample of 4121 SMEs from the services, trade and manufacturing sectors, located in Mexico. The data was collected through an online questionnaire addressed to the SMEs manager through the LimeSurvey platform. The field work will be carried out from January to July 2022. The PLS-SEM statistical technique was used to test the hypotheses of the proposed theoretical model. The data show that digital transformation plays an important role in a more decisive way in technological innovation and non-technological innovation; In addition, it is also proven that innovation in its two modalities has significant effects on the financial performance results of Mexican SMEs. However, we have found that digital transformation has a small effect on the financial performance of these companies. On the other hand, the study shows that the sustainability strategy plays the role of a moderating variable, positively affecting technological innovation and non-technological innovation. Furthermore, the study explains that the male gender is the one that has had the best results in innovation and financial performance. The study contributes to the development of the theory of dynamic capabilities supported by the innovation model (DUI and STI).
Keywords: 650; Digital transformation; technological/ non-technological innovation; SMEs